Systems Modeling Language (SysML v2) Support for Digital Engineering. Issue 1 (12th April 2022) - Bajaj, Manas; Friedenthal, Sanford; Seidewitz, Ed
ABSTRACT: The OMG Systems Modeling Language™ (SysML®) was adopted in 2006 and has been used by many organizations to support their efforts to transition to a model‐based systems engineering (MBSE) approach. SysML v2 is the next generation Systems Modeling Language and is intended to address many of the limitations of SysML v1. This paper highlights how the SysML v2 language and the new standard Application Programming Interface (API) can enable MBSE and digital engineering. SysML v2 is being developed by the SysML v2 Submission Team (SST) in response to requirements issued by the Object Management Group (OMG). The final submission to the OMG is planned for 2022. The draft SysML v2 specifications and the open‐source SysML v2 pilot implementation can be found at https://github.com/Systems-Modeling .